HgTe Nanocrystals Carrier Density and Its Tuning - Mariarosa Cavallo; Dario Mastrippolito; Clément Gureghian; Erwan Bossavit; Huichen Zhang; Albin Colle; Tommaso Gemo; Alexandre Neyret; Adrien Khalili; Debora Pierucci; Emmanuel Lhuillier (Small Structures)
HgTe nanocrystals (NCs) are now an established material for colloidal optoelectronics. In the mid‐ and far‐infrared range, there is to date no viable colloidal alternative material that can emit or detect light with such a high efficiency. Advancements have been rapid, primarily concentrating on the direct application of the narrow bandgap material spectrum in devices. However, certain material properties, such as carrier density, have been suboptimally addressed, despite their critical importance to device design. Therefore, this review aggregates most of the recent developments related to the determination and control of the carrier density with HgTe NCs. The manuscript is organized along three scales: the intrinsic properties that mostly relate to the inorganic core of the NCs, the nanoscale functionalization that relates to the surface modification of the NCs, and the device scale mostly driven by gating methods. The review provides a systematic discussion on strategies and technologies to control the carrier density and their use for optoelectronics. Finally, a discussion is done on the directions to be developed to push even further the efficiency of devices based on this material.